KAJIAN MODEL PEMBELAJARAN E-LEARNING SEBAGAI ENABLER DALAM MENINGKATKAN KREATIVITAS BELAJAR DAN KOMPETENSI TIK MAHASISWA - Lumba, Ester (Teknik dan Ilmu Komputer, 2012)
The mastery of communication and information technology has become a crucial matter for every computer science graduates in Indonesia. For this reason, a research on e-learning model was conducted aiming at finding out whether the model can be an enabler to improve the studentsâ learning creativity and competence. This research implemented confirmatory research method using Structural Equation Modeling (SEM) as the statistical analysis tool to test the hypothesis. SEM is applied to study the relation between the construct and the indicators used to measure the construct. The writer used the AMOS 6.0 software in the data processing. The data collected from the questionnaire were primary data since they came from the students as the main source. The research findings were expected to offer additional references for educational institutions as well as lecturers in Indonesia to adapt learning technologies to improve studentsâ creativities and competences. Â Â Keywords: e-learning, enabler, creativity, competence, open source